2015
DOI: 10.1038/pr.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic postconditioning reduces microglial activation, astrocyte and caspase activity, and inflammatory markers after hypoxia–ischemia in the neonatal rat brain

Abstract: Background: Postconditioning (PostC) with mild hypoxia shortly after a neonatal hypoxic-ischemic (HI) brain injury can reduce brain damage, however, the mechanisms underlying this protection are not known. We hypothesize that hypoxic PostC reduces brain markers of glial activity, inflammation, and apoptosis following HI injury. Methods: Sprague Dawley rat pups were exposed to right common carotid artery occlusion and hypoxia (7% oxygen, 3 h) on postnatal day 7 and 24 h later, pups were exposed to hypoxic PostC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…Consistent with previous reports (Chavez-Valdez et al, 2012;Qiu et al, 2007;Teo et al, 2015) we observed HI-induced astrocyte activation in the ipsilateral hippocampus. This astroglial response, which persists for at least 6 weeks after HI, was ameliorated by intranasal C3a treatment in a region specific manner.…”
supporting
confidence: 93%
“…Consistent with previous reports (Chavez-Valdez et al, 2012;Qiu et al, 2007;Teo et al, 2015) we observed HI-induced astrocyte activation in the ipsilateral hippocampus. This astroglial response, which persists for at least 6 weeks after HI, was ameliorated by intranasal C3a treatment in a region specific manner.…”
supporting
confidence: 93%
“…In the CNS, Microglia are a major glial component and exhibit the function of immune-surveillance in a resting state. However, when the HI event occurs, microglia are strongly activated and release inflammatory factors contributing to inflammatory process in the brain gray matter [ 35 , 37 ]. In our study, we did find that the number of Iba-1 immunostaining cells was significantly increased in the cortex and hippocampus after HI, which indicated that microglia were activated by the HI insult.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines in the CNS are primarily derived from immune cells. Microglia are a major component of the immune cells in the CNS and strongly activated in the neonatal brain [3, 44, 46, 47]. When an ischemic event occurs, microglia are activated, and they release inflammatory factors leading to the deterioration of the injury.…”
Section: Discussionmentioning
confidence: 99%